2017
DOI: 10.1038/srep45851
|View full text |Cite
|
Sign up to set email alerts
|

Differences in peripheral sensory input to the olfactory bulb between male and female mice

Abstract: Female mammals generally have a superior sense of smell than males, but the biological basis of this difference is unknown. Here, we demonstrate sexually dimorphic neural coding of odorants by olfactory sensory neurons (OSNs), primary sensory neurons that physically contact odor molecules in the nose and provide the initial sensory input to the brain’s olfactory bulb. We performed in vivo optical neurophysiology to visualize odorant-evoked OSN synaptic output into olfactory bub glomeruli in unmanipulated (gona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 87 publications
4
39
0
Order By: Relevance
“…In vivo optical imaging was performed (Czarnecki, Moberly, Rubinstein, Turkel, Pottackal, & McGann, 2011; Czarnecki, Moberly, Turkel, Rubinstein, Pottackal, Rosenthal et al, 2012; Fast & McGann, 2017; Kass, Czarnecki, Moberly, & McGann, 2017; Kass, Guang, Moberly, & McGann, 2016; Kass, Moberly, & McGann, 2013a; Kass, Moberly, Rosenthal, Guang, & McGann, 2013b; Kass, Pottackal, Turkel, & McGann, 2013c; Kass et al, 2013d) to visualize odor-evoked GCaMP signals from GAD65-expressing PG interneurons (Figure 1G–I) before and after conditioning (Figure 1A). Vapor dilution olfactometry was used during imaging (Czarnecki et al, 2011; Czarnecki et al, 2012; Kass et al, 2017; Kass et al, 2016; Kass et al, 2013a; Kass et al, 2013b; Kass et al, 2013c; Kass et al, 2013d) to present up to 3 concentrations of up to 5 monomolecular odorants that have no known innate valence.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In vivo optical imaging was performed (Czarnecki, Moberly, Rubinstein, Turkel, Pottackal, & McGann, 2011; Czarnecki, Moberly, Turkel, Rubinstein, Pottackal, Rosenthal et al, 2012; Fast & McGann, 2017; Kass, Czarnecki, Moberly, & McGann, 2017; Kass, Guang, Moberly, & McGann, 2016; Kass, Moberly, & McGann, 2013a; Kass, Moberly, Rosenthal, Guang, & McGann, 2013b; Kass, Pottackal, Turkel, & McGann, 2013c; Kass et al, 2013d) to visualize odor-evoked GCaMP signals from GAD65-expressing PG interneurons (Figure 1G–I) before and after conditioning (Figure 1A). Vapor dilution olfactometry was used during imaging (Czarnecki et al, 2011; Czarnecki et al, 2012; Kass et al, 2017; Kass et al, 2016; Kass et al, 2013a; Kass et al, 2013b; Kass et al, 2013c; Kass et al, 2013d) to present up to 3 concentrations of up to 5 monomolecular odorants that have no known innate valence.…”
Section: Methodsmentioning
confidence: 99%
“…Vapor dilution olfactometry was used during imaging (Czarnecki et al, 2011; Czarnecki et al, 2012; Kass et al, 2017; Kass et al, 2016; Kass et al, 2013a; Kass et al, 2013b; Kass et al, 2013c; Kass et al, 2013d) to present up to 3 concentrations of up to 5 monomolecular odorants that have no known innate valence. The odor-panel was selected based on previous experiments (Kass et al, 2013b; Kass et al, 2013d), and included 3 esters (MV, which was used as the CS, EV, and BA), 1 ketone (2H), and 1 aldehyde (t rans -2-methyl-2-butenal, 2M2B), yielding 3 odor categories for paired and odor-alone subjects (training ester, unexposed esters, and unexposed “other”) and 1 odor category for shock-alone subjects (unexposed odors).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the lack of clear sex differences in the MOE, a recent study 89 in mice comparing the OSN response to a variety of monomolecular odorants showed that odor-induced signaling was more rapid and affected more MOB glomeruli in females than males. Curiously, these responses were decreased by gonadectomy in females, but increased in males.…”
Section: Main Olfactory Epitheliummentioning
confidence: 99%